Increasing EFL Students’ Responsibility with Learning Activities through Project Work - Toro Bustamante, Carlos Augusto (Íkala, Revista de Lenguaje y Cultura, 2007)
This action research project highlights the increased responsibility of Grade 7 students when implementing project work in an English foreign language classroom, in a public, co-ed school in Colombia. The action research was carried out over fi ve months and the results show the positive attitudes and behavior that students displayed towards project work in class, the importance of scaffolding to students’ confi dence with class activities, and good grades with positive feedback enhancing students’ learning. Diffi culties found related to cancelled classes, and students’ negative attitudes when groups were assigned by the teacher, along with unequal group work distribution. Received: 28-03-07 / Accepted: 05-08-07 How to reference this article: Toro Bustamante, C. A. (2007). Increasing EFL Students’ Responsibility with Learning Activities through Project Work. Íkala. 12(1), pp. 212 – 242.